2008
DOI: 10.2535/ofaj.85.91
|View full text |Cite
|
Sign up to set email alerts
|

The presence of intra-tubular lymphocytes in normal testis of the mouse

Abstract: Summary: Spermatoza contain various autoimmunogenic materials, which are recognized as foreign by the self immune system. Therefore, the blood-tesits-barrier (BTB) formed by Sertoli cells, basal lamina and myoid cells protects autoimmunogeneic spermatozoa from attack by the self immune system. However, the BTB at the tubuli recti (TR) and the rete testis (RT) is known to be incomplete against humoral substances. We investigated here whether the BTB is physiologically penetrated by lymphocytes in mice. We perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Similarly, in urology, the testis is no longer considered an immune-privileged site. A layer of epithelial sertoli cells, which are interconnected by tight junctions, encloses the testis germinal compartment, and though leukocytes are strictly blocked from the lumen of the seminiferous tubules in normal tissue, they occasionally penetrate the blood-testis barrier (BTB) of tubuli recti [ 54 , 55 ]. In addition, the testis has a BTB gating system at the seminiferous tubule [ 2 ].…”
Section: Lessons From Neuroimmunology: the Role Of The Circulating Immentioning
confidence: 99%
“…Similarly, in urology, the testis is no longer considered an immune-privileged site. A layer of epithelial sertoli cells, which are interconnected by tight junctions, encloses the testis germinal compartment, and though leukocytes are strictly blocked from the lumen of the seminiferous tubules in normal tissue, they occasionally penetrate the blood-testis barrier (BTB) of tubuli recti [ 54 , 55 ]. In addition, the testis has a BTB gating system at the seminiferous tubule [ 2 ].…”
Section: Lessons From Neuroimmunology: the Role Of The Circulating Immentioning
confidence: 99%
“…This loss of fully differentiated gametes, reported in a wide range of vertebrates from reptiles (Akbarsha et al, ; Rheubert et al, ) and birds (Aire, ) to mammals (Holstein, ; Goyal, ), has been largely ascribed to the spermiophagic activities of the rete testis and ductuli efferentes (efferent ductules). Studies mainly mice have shown that the latter two networks of ductules are immunologically more challenging relative to the protected, plasma‐free milieu of the spermatogenic tubules (Holstein, ; Naito and Itoh, ; Naito et al, ) due to the common occurrence of subepithelial and intraepithelial leukocytes in these intratesticular passageways. How much these immune cells contribute to this loss of spermatozoa generally in vertebrates is unclear as they have not been reported in all studied vertebrates, supposedly totally absent or not referred to at all in the regressing or quiescent ductuli efferentes in a range of seasonal breeding mammals and reptiles (Pudney and Fawcett, ; Peirce and Breed, ; Guerrero et al, ; Rheubert et al, ; Waqas et al, ).…”
mentioning
confidence: 99%